Perancangan Aplikasi Pengamanan Data Menggunakan Algoritma RSA (Rivest Shamir Adleman) dan AES (Advanced Encryption Standard) Berbasis Web - Dika Alfiani Fauzan; Ahmad Fathurrozi; Sugiyatno (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Cryptography is a method of manipulating a secret message into an unknown form to many people, with the aim of protecting the secret message from unauthorized individuals. Various types of cryptographic algorithms can be applied to protect data and information. Among them are the RSA (Rivest Shamir Adleman) and AES cryptographic algorithms. AES and RSA are often used together to provide optimal security. AES is used for efficient data encryption, while RSA is used for key exchange and digital signatures. In this research, AES is used for encrypting and decrypting documents/data, while RSA serves as the encryption and decryption for the AES key, which acts as the encryptor and decryptor for the documents/data. With this combination, the strengths of both algorithms can be utilized to achieve strong data security and confidentiality. The author aims to implement data security at XYZ Company. In this research, the author focuses on securing procedure documents and calibration methods.